From Posts to Preferences: The Mediating Role of Brand Image in KOL and Instagram Influence on Stay Decisions - Pane, Asty Kesuma Dinasty; Tuti, Meylani; Riyanto, Agus (Technium Social Sciences Journal, 2025)
This study aims to analyze the influence of key opinion leaders (KOL) and Instagram on the decision to stay through brand image. The population in this study was guests who stayed at the hotel from November 2024 to January 2025. The sampling technique used was accidental sampling, namely, guests who met directly with the researcher. data collection was carried out using a Google form and obtained 259 respondents. Data analysis used the structural equation model (SEM) method with the help of Smart PLS 3 software. The results showed that key opinion leaders and Instagram had a significant and positive influence on the decision to stay, both directly and indirectly. Likewise, key opinion leaders and Instagram had a significant and positive influence on brand image. Brand Image is a mediator between key opinion leaders and Instagram that influences the decision to stay. The implications in this study can be used by hotel owners as a reference to be able to analyze and determine hotel marketing strategies through the Instagram social media platform in the form of interesting content about hotel information, including information about hotel facilities, hotel prices, hotel locations and other interesting places around the hotel, packaged and presented by key opinion leaders with a wide target reach, especially to their followers who aim to be able to increase the visibility of the audience and strive to increase hotel revenue.